Mineralisation of Developmentally Hypomineralised Human Enamel in vitro - Crombie, F.A.; Cochrane, N.J.; Manton, D.J.; Palamara, J.E.A.; Reynolds, E.C. (Caries research, 2013)
Molar-incisor hypomineralisation (MIH) is a problematic and costly condition. Caries remineralising agents are often recommended for MIH management despite the lack of evidence that these lesions have the capacity for increasing their mineral content. Following surface layer removal ± NaOCl pre-treatment and 14-day exposure to a CPP-ACFP solution at pH 5.5, MIH lesions were analysed using transverse microradiography and polarised light microscopy. Lesions were highly variable but treatment with the remineralising solution increased mineral content (1,828 ± 461 vol% min·µm, %R = 17.7 ± 5.7) and porosity decreased demonstrating the proof of concept that the mineral content of developmentally hypomineralised enamel can be improved after eruption.